Effects of drilling strategies for CFRP/Ti stacks on static mechanical property and fatigue behavior of open-hole CFRP laminates. (April 2021) - An, Qinglong; Zhong, Bingfu; Wang, Xianfeng; Zhang, Hongzhou; Sun, Xiaofeng; Chen, Ming
Abstract: Hybrid carbon fiber reinforced polymer (CFRP)/titanium alloy (Ti) stacks are the key load-bearing components in the aircraft structure. However, CFRP/Ti stack has poor machinability and defects are easily caused in the drilling process, resulting in the reduction of fatigue performance for aircraft structural parts. In this paper, the effects of drilling strategies on static mechanical property and fatigue behavior of open-hole CFRP laminates were studied by quasi-static tensile tests and fatigue tests. When drilling CFRP/Ti stacks from CFRP side, due to the hole defects of CFRP caused by Ti6Al4V chips, the ultimate tensile strength and fatigue life of open-hole CFRP laminates decrease by 12.5 % and 75.8 %, respectively. When drilling CFRP/Ti stacks from Ti6Al4V side, due to the drilling defects of CFRP caused by the high drilling temperature and delamination, the ultimate tensile strength and fatigue life of open-hole CFRP laminates decrease by 5.8 % and 26.5 %, respectively.